Editorial: Thoughts on the Possible Realignment of the Christian Right in Twenty-first Century America - Davis, Derek H. (A journal of church and state, 1999)
Derek H. Davis; Editorial: Thoughts on the Possible Realignment of the Christian Right in Twenty-first Century America, Journal of Church and State, Volume 41,